ChemInform Abstract: A Co‐Operative Ni—Cu System for C(sp)—C(sp) and C(sp)—C(sp2) Cross‐Coupling Providing a Direct Access to Unsymmetrical 1, 3‐Diynes and En‐ynes. Issue 16 (April 2015) - Mukherjee, Nirmalya; Kundu, Debasish; Ranu, Brindaban C.
Abstract 29 examples